CLAY SLATES – EFFECTIVE MINERAL RAW MATERIALS FOR PRODUCTION OF CONSTRUCTION MATERIALS - V. U. Matsapulin; A. B. Toturbiev; V. I. Cherkashin (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
This paper gives a brief analysis of the use efficiency of non-metallic materials, mainly shale, which are in great demand and have a low cost in production of building materials. The results of experimental studies of production of the multifunctional low-calcination bulk ceramic material from shale are presented.